Génération SIDA : le mensuel de la prévention et de l'information sur le SIDA. (Paris : EURL de Presse, 1995)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks?Redactie : 49 rue Richelieu, 75001 Paris
Frans
Periodiek